Personalized Precision Medicine (PPM): A Tailored Treatment Approach for the Betterment of Prognosis in Oral Carcinoma: A Systematic Review - Sandeep Pagare; Naveen Shetty; Ketaki Bhor; Anindita Chakraborty; Mandavi Waghmare; Hemant Bhutani (Journal of Indian Academy of Oral Medicine and Radiology)
Background: The Personalized Precision Medicine (PPM) MODEL encompasses a custom-built treatment modality incorporating immunotherapy in the form of Monoclonal antibodies, checkpoint inhibitors, cytokines, hematopoietic stem cell transplants predominantly, and Chimeric Antigen Receptor T-cell (CART) therapies. Biomarkers, companion diagnostics, and Organoids are major tools in PPM to develop patient-specific databases, delivering patient-specific medicines for a targeted approach. Objective: To assess how efficacious personalized precision medicine can be in the betterment of prognosis comparison to traditional treatment strategies when treating oral cancer. Methods: Comprehensive search with PubMed, Cochrane library, Web of Science, Embase, and EBSCO health. ProQuest and Google scholar was looked up to find any further gray literature that might have been missed. After thoroughly assessing the studies for eligibility criteria, data were extracted by two reviewers, and a detailed quality check of the selected records was assessed via the Cochrane risk of bias-2 tool. Results: Nine articles were included in the systematic review after thorough screening and the removal of duplicates, by analyzing the title and abstract, concentrating on the connection between genomics and precision medicine and their effects on oral cancer. Conclusions: The advanced personalized precision medicine (PPM) ecosystem amalgamates established clinical data with genetic molecular profiling to fabricate tailored treatment plans for individual patients, thereby significantly improving prognosis.